2023
DOI: 10.2478/tar-2023-0021
|View full text |Cite
|
Sign up to set email alerts
|

Automated Eddy Current System for Aircraft Structure Inspection

Iuliia Lysenko,
Yurii Kuts,
Valentyn Petryk
et al.

Abstract: Aircraft part diagnostics are crucial during both production and maintenance, with eddy current nondestructive testing (ECNDT) being the method of choice due to its cost-effectiveness, informativeness, productivity, and reliability. ECNDT excels regardless of surface condition or coatings. It’s employed for diagnosing various aircraft components, necessitating diverse transducer types, excitation modes, and advanced signal processing. To improve ECNDT, this article explores integrating harmonic and impulse exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…The complex interplay of factors, including array size, geometry, material properties, and inspection parameters, demands comprehensive evaluation [7,10]. This study addresses challenges identified in previous research by providing experimental insights into optimizing ECA performance for enhanced defect detection in aircraft components [7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The complex interplay of factors, including array size, geometry, material properties, and inspection parameters, demands comprehensive evaluation [7,10]. This study addresses challenges identified in previous research by providing experimental insights into optimizing ECA performance for enhanced defect detection in aircraft components [7,11,12].…”
Section: Introductionmentioning
confidence: 99%